ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI POLA BILANGAN BERDASARKAN TAHAPAN NEWMAN PADA KELAS VIII SMP NEGERI 10 PRAYA BARAT - Azizah, Baiq Wakiatul; Sarjana, Ketut; KERTIYANI, Ni; Laila Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the mistakes of grade VIII students of SMP Negeri 10 Praya Barat in solving the number pattern material story problem based on Newman's error stages. The method used in this study is qualitative descriptive. Data collection was carried out using written test and interview methods. The subjects in this study were grade VIII students of SMP Negeri 10 Praya Barat measuring 26 students. The results showed that the percentage of errors made by students in solving story problems related to number pattern material based on Newman stages were: (a) the percentage of reading errors made by students is 22.43%, (b) the percentage of misunderstanding problems is 58.33%, (c) the percentage of transformation errors is 74.44%, (d) the percentage of process skill errors is 88.46%, (e) the percentage of final answer writing errors is 62.17%. While the total error of all grade VIII students of SMP Negeri 10 Praya Barat with a percentage, 65.52% is classified as a high category. The factors that cause student errors are students not carefully reading the questions, not carefully finding things known in the questions, not knowing the problems in the questions, not knowing the formulas that should be used and following the answers of friends.